Direct radical scavenging activity of benzbromarone provides beneficial antioxidant properties for hyperuricemia treatment - Kadowaki, D.; Sakaguchi, S.; Miyamoto, Y.; Taguchi, K.; Muraya, N.; Narita, Y.; Sato, K.; Chuang, Victor; Maruyama, T.; Otagiri, M.; Hirata, S. (Pharmaceutical Society of Japan, 2015)
Uric acid exerts an important antioxidant effect against external oxidative stress under physiological conditions. However, uric acid itself can increase oxidative stress via reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation in adipocytes and vascular cells. Uric acid transporter 1 is involved in the generation of this oxidative stress. Furthermore, uric acid locally activates the renin-angiotensin system, thus producing angiotensin II and subsequently increasing intracellular oxidative stress. Ben-zbromarone has been reported to suppress uric acid reabsorption via uric acid transporter 1 inhibition in renal tubular cells. In this study we evaluated the in vitro antioxidant effect of benzbromarone from several perspectives. First, the direct radical-trapping capacity of benzbromarone was measured by chemilumines-cence assay and electron paramagnetic resonance spectroscopy. Second, the intracellular antioxidant activity of benzbromarone in hyperuricemia was evaluated using endothelial cells. In light of these results, benz-bromarone is hypothesized directly to scavenge the superoxide anion radical. In addition, benzbromarone inhibited reactive oxygen species production that was induced by angiotensin II or uric acid in endothelial cells. These findings suggest that benzbromarone possesses the ability directly to scavenge radicals and may act as an antioxidant against uric acid and angiotensin II-induced oxidative stresses in endothelial cells at therapeutically achievable levels in blood.